A Plethora of Roles Played by Teacher Unions in Fostering Improved Learning Environment in Schools in Zambia - Sinkala, Henry; Simui, Francis; Muleya, Gistered (Advances in Social Sciences Research Journal, 2022)
The study explores a myriad of roles played by Teacher Unions in fostering improved learning environment in selected schools of Lusaka, district, Zambia. A case study design was employed on a target population that comprised 28 participants from primary and secondary schools and teacher unions. Expert Purposive sampling technique was applied to sample participants from teacher union officials in Lusaka District. Data generated through interviews; Focus Group Discussion; and Document Review were thematically analyzed. Emergent from this study is a plethora of roles played by teachers’ unions such as participation in education policy making process, defending teacher members, presiding over disputes between member and the employer and improving peaceful learning environment in schools among others. In addition, Unions were actively engaged in fighting for professional recognition for teachers as well as fairness in promotion. Unions were involved in advocacy in relation to education reforms and teachers’ professional output as well as learner achievement in examinations. Thus, it is recommended among others that, Teacher Unions should enhance their knowledge and skills set to effectively deliver on various divergent mandate areas on behalf of their membership.